2015
DOI: 10.4172/2161-0991.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Standard Formulae in Predicting Liver Volumes: A South East Asian Series of Adult Living Donors

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies reported a significant correlation between the predicted liver volume and the actual volume, or the actual weight of the liver. 16,20 Unfortunately, most of the data were derived from healthy liver grafts of living donors. There was a study on CT volumetry in patients who underwent partial liver resection; however, this study did not take the presence of liver cirrhosis into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported a significant correlation between the predicted liver volume and the actual volume, or the actual weight of the liver. 16,20 Unfortunately, most of the data were derived from healthy liver grafts of living donors. There was a study on CT volumetry in patients who underwent partial liver resection; however, this study did not take the presence of liver cirrhosis into account.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies suggested that this number might not be appropriate, and alternative methodsranging from a different conversion factor to a more complex formula-were proposed. 16,19,20,25 Nevertheless, these suggestions came from studying normal livers and did not account for the presence of liver cirrhosis. In the current study, we proposed a formula that can accurately predict the weight of the resected cirrhotic liver (R-squared =0.914).…”
Section: Discussionmentioning
confidence: 99%